2002
DOI: 10.1143/jjap.41.6653
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxial Growth of a (101) Pb(ZrxTi1-x)O3Film on an Epitaxial (110) Ir/(100) ZrN/(100) Si Substrate Structure

Abstract: AbstmLThe model of plastic phenomena in glasses is developed. St~ctural defecIs mnnected with the molecular states with a double-well potential are introduced. On the basis of this mncept it turns out to be possible to explain the characteristic features of the deformation process The value of the limit of proportionalily, yielding limit and angle of pmpagation of shear bands are estimated for a twodimensional glass. The recults obtained are compared with the experimental dam wailable and considerable agreemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…However, it has been generally believed that, to obtain epitaxial ZrN films on Si substrate, a fairly high substrate temperature of approximately 6002900 C is required [7][8][9], which is too high for practical use in the microelectronics industry. In addition, Barnett et al [9] reported that cracks were observed in ZrN films prepared at high substrate temperature because the lattice misfit between ZrN and Si is 16% and the thermal expansion coefficient ð7:24 Â 10 À6 = CÞ of ZrN is much higher than that of Si ð2:33 Â 10 À6 = CÞ.…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been generally believed that, to obtain epitaxial ZrN films on Si substrate, a fairly high substrate temperature of approximately 6002900 C is required [7][8][9], which is too high for practical use in the microelectronics industry. In addition, Barnett et al [9] reported that cracks were observed in ZrN films prepared at high substrate temperature because the lattice misfit between ZrN and Si is 16% and the thermal expansion coefficient ð7:24 Â 10 À6 = CÞ of ZrN is much higher than that of Si ð2:33 Â 10 À6 = CÞ.…”
Section: Introductionmentioning
confidence: 99%
“…There have been many experimental studies on depositing epitaxial PZT thin films on single-crystal oxide [4][5][6][7][8][9][10][11] and silicon substrates [12][13][14][15][16][17][18][19]. To develop ferroelectric capacitors, a ferroelectric thin film must be deposited on a conducting material.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on what references [12][13][14][15][16][17][18][19] are cited, the polarization of epitaxial PZT capacitors on silicon is rather small compared with that of epitaxial PZT capacitors on MgO or STO. To understand this dependence, it is very important to evaluate epitaxial PZT capacitors in same structure on different substrates such as Si and MgO.…”
Section: Introductionmentioning
confidence: 99%